Pengembangan Bahan Ajar Cetak Berorientasi Kearifan Lokal dalam Materi “Negaraku Indonesia” pada Siswa Kelas IV SDN 14 Pontianak Selatan - Vivi Niyarti; Asmayani Salimi; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2024)
This research and development aims to produce local wisdom-oriented printed teaching material products in the material